2012
DOI: 10.1080/02640414.2012.676665
|View full text |Cite
|
Sign up to set email alerts
|

The BASES Expert Statement on use of music in exercise

Abstract: This is an Author's Accepted Manuscript of an article published in Journal of Sports Sciences, 30(9), 953-956, 2012, copyright Taylor & Francis, available online at: http://www.tandfonline.com/10.1080/02640414.2012.676665.The use of music during exercise has become ubiquitous over the past two decades and is now supported by a burgeoning body of research detailing its effects and the contingencies surrounding its use. The purpose of this statement is to present a synopsis of the body of knowledge, with selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 20 publications
1
76
0
3
Order By: Relevance
“…For these individuals it is important to identify meaningful performer-environment relationships for pacing and how these relationships might change as a function of practice, training, or habituation. For example, research has shown that in repetitive endurance type activities self-selected, motivational, and stimulating music enhance affect, reduce ratings of perceived exertion, improve energy efficiency, leading to increased work output [135,136]. Identifying affordances that can help participants overcome a strong urge (affordance) to stop continuation of their exercise program, especially in the early stages, can in this way be a very important application in health sciences.…”
Section: Discussionmentioning
confidence: 99%
“…For these individuals it is important to identify meaningful performer-environment relationships for pacing and how these relationships might change as a function of practice, training, or habituation. For example, research has shown that in repetitive endurance type activities self-selected, motivational, and stimulating music enhance affect, reduce ratings of perceived exertion, improve energy efficiency, leading to increased work output [135,136]. Identifying affordances that can help participants overcome a strong urge (affordance) to stop continuation of their exercise program, especially in the early stages, can in this way be a very important application in health sciences.…”
Section: Discussionmentioning
confidence: 99%
“…Studies had shown that the collective form of movement [44], music mediated sports training [45] and home exercise training [46] could improve older patients exercise motivation, so choose a collective form of exercise, music mediated sports training and family-style campaign training and other forms may be effective to improve the adherence in elderly with DPN.…”
Section: Adherence Of Exercisementioning
confidence: 99%
“…Accentuated bass frequencies are thought to increase arousal during sport exercises (Karageorghis, Terry, Lane, Bishop, & Priest 2012), perhaps pointing to movement-induction effects of low frequency instruments on experienced groove that may be dissociated from potential timing mechanisms. Falling along the lines of arousal are suggestions that loud music, and in particular the low frequency aspects thereof, may activate the vestibular system thus creating more extensive sensory stimulation at periodicities corresponding to the underlying beat, and promoting entrainment (Todd & Cody, 2000;van Dyck et al, 2013).…”
Section: Audio Features Of Groove 29mentioning
confidence: 99%